Mechanical performance of a dry mortar without cement, based on paper fly ash and blast furnace slag. (March 2019) - Seifi, Sahar; Sebaibi, Nassim; Levacher, Daniel; Boutouil, Mohamed
Abstract: In recent years, the innovations in the construction industry have developed remarkably. Using the waste materials and co-products coming from different industries, became an alternative to recycle and producing new eco-friendly materials from the wastes left behind by the industries. In present study, Wastepaper Sludge Ash (WSA) and Ground Granulated Blast-furnace Slag (GGBS) which is known, as a cement replacement and cementitious material in construction industry in recent research, are the by-products reused. They mixed and activated to obtain a binder matrix for manufacturing dry-mortars in construction industry. The objectives are to valorize the maximum reuse of WSA and to substitute cement in the mortar composition and also to recycle and reuse wastes in respect of circular economy. This paper aimed to observe the mechanical properties of these innovated mortars. The binder matrix for dry-mortar manufacturing is a non-cement matrix and is composed of 72 wt% of WSA and 28 wt% of GGBS, considering that GGBS should be 7% of total mass of the mixture without cement, water and any activators addition. Two types of non-cement mortars have been investigated. Mortars without any activators and the ones with three types of activators to improving the maximum reactivity at early age. These activators are: sodium carbonate, sodium silicate and calcium chloride. WSA contains 20% SiO2 and 50% CaO, and respectively 35% and 43% for GGBS, which are close to the one of cement and that can develop pozzolanic properties in the absence of cement. The condition of curing is carried out at 20 °C, for 2, 7 and 28 days for all the prismatic samples with the dimension of 40 × 40 × 160 mm 3 . Mechanical tests i.e. compression and tension by bending, are performed after 2, 7 and 28 days to determine the mechanical strengths compared with those of normal mortars. A maximum compressive strength for non-cement binder matrix is 13.7 and 11.1 MPa, which obtained in the presence of calcium chloride and sodium silicate respectively after 28 days. Highlights: Dry mortars based on co-products of industry have been formulated in the interest of waste recycling. New method of laboratory compaction was explored. The effects of several activators on compressive strength were investigated.